FUNCTION AND DISEASES OF THE THYROID GLAND - Golijan, Radojka (ACADEMIC REVIEW, 2021)
The thyroid gland is the gland with internal secretion or endocrine gland. It secretes hormones T3 (triothyrosine), T4 (thyroxine). Their secretion as well as the overall functioning of the thyroid gland is under the influence of the pituitary gland. The pituitary gland is also endocrine gland that can be called "direignetom" of all endocrine glands. The influence of the pituitary gland on the thyroid gland is based on the feedback principle. If the secretion of T3 and T4 is reduced, the pituitary gland through TSH (thyroid-stimulating hormone) stimulates the secretion of these thyroid hormones, or if their secretion is increased, it also acts through TSH hormones to slow down and reduce the secretion of T3 and T4. Thyroid-stimulating hormone (TSH) has a stimulating or inhibitory effect on thyrocytes (active thyroid endocrinology tissue) depending on whether more secretion is required or reduced secretion of thyroid hormone is required.